Multiple Respiratory Syncytial Virus Introductions Into a Neonatal Intensive Care Unit. (4th April 2020) - Rose, Erica Billig; Washington, Erica J; Wang, Lijuan; Benowitz, Isaac; Thornburg, Natalie J; Gerber, Susan I; Peret, Teresa C T; Langley, Gayle E
Abstract: Background: Outbreaks of respiratory syncytial virus (RSV) in neonatal intensive care units (NICUs) are of concern because of the risk of severe disease in young infants. We describe an outbreak of RSV in a NICU and use whole genome sequencing (WGS) to better understand the relatedness of viruses among patients. Methods: An investigation was conducted to identify patients and describe their clinical course. Infection control measures were implemented to prevent further spread. Respiratory specimens from outbreak-related patients and the community were tested using WGS. Phylogenetic trees were constructed to understand relatedness of the viruses. Results: Seven patients developed respiratory symptoms within an 11-day span in December 2017 and were diagnosed with RSV; 6 patients (86%) were preterm and 1 had chronic lung disease. Three patients required additional respiratory support after symptom onset, and none died. Six of 7 patients were part of the same cluster based on > 99.99% nucleotide agreement with each other and 3 unique single-nucleotide polymorphisms were identified in viruses sequenced from those patients. The seventh patient was admitted from the community with respiratory symptoms and had a genetically distinct virus that was not related to the other 6. Implementation of enhanced infection control measures likely limited the spread. Conclusions: Using WGS, we found 2 distinct introductions of RSV into a NICU, highlighting the risk of healthcare-associated infections during RSV season. Early recognition and infection control measures likely limited spread, emphasizing the importance of considering RSV in the differential diagnosis of respiratory infections in healthcare settings. Abstract : Using whole genome sequencing, we found 2 introductions of respiratory syncytial virus (RSV) into a neonatal intensive care unit causing 7 infections. This outbreak highlights the risk of healthcare-associated infections during RSV season; early recognition is critical to limit transmission.